Phase-based analysis to determine first order decay rates for a bioreactor landfill - Nwaokorie, Kelechi J., author; Bareither, Christopher A., advisor; Sharvelle, Sybil E., advisor; von Fischer, Joseph C., committee member (Colorado State University. Libraries, 2017)
In recent years, the goal of municipal solid waste (MSW) landfill management has transitioned from waste sequestration to waste stabilization. A bioreactor landfill is an MSW landfill operated with a deliberate goal to achieve waste stabilization via in situ organic waste decomposition. Enhanced landfill gas (LFG) generation that results from moisture addition to increase the rate of anaerobic biodegradation can have different consequences on landfill operations. Additionally, landfills commonly are constructed and filled in phases (i.e., delineated areas of the landfill where waste is placed) that are operated with different moisture enhancement strategies. Thus, there is a need to simulate and predict LFG generation in a bioreactor landfill on a phase-specific basis to more accurately assess waste decomposition and progression of organic waste stabilization. In this study, site-wide and phase-specific LFG modeling was conducted for a bioreactor landfill. A phase-specific LFG modeling approach was developed and used to assess six separate phases of the landfill. This approach included a temporal estimate of waste disposal and separation of LFG collection data for the six phases. Landfill gas collection in each phase was used to compute methane collection based on gas composition analyses and used to estimate methane generation based on two considerations of collection efficiency: constant collection efficiency of 85% and temporally varying collection efficiency. Methane generation was predicted using the U.S. EPA LandGEM. Model simulations were compared with adjusted methane collection data to optimize the first-order decay rate (k), which was the primary variable used to assess waste decomposition and stabilization. First-order decay rates were optimized for site-wide and phase-specific analyses that considered (i) monthly versus annual averaging techniques for LFG data, (ii) collection efficiencies, and (iii) LFG collected only in the gas wells versus LFG collected in gas wells and perforated pipes in leachate collection and recirculation systems. The recommended gas modeling approach is to use monthly average LFG flow rates, a constant collection efficiency of 85%, and LFG collected from gas wells and leachate collection / recirculation systems. The optimized k for the site-wide analysis was 0.078 1/yr, whereas the default k for conventional MSW landfills with no moisture enhancement is 0.04 1/yr. Thus, the site-wide k supports enhanced organic waste biodegradation and stabilization. The optimized ks for the phase-specific analyses ranged between 0.025 and 0.13 1/yr, which suggest that although the overall site was operating at an enhanced rate of waste decomposition, the rate varied between landfill phases. Moisture addition via leachate recirculation and liquid waste addition was implemented at the landfill for the five more recent phases. The k values for these five phases increased with increasing liquid addition per waste mass whereby the optimized k values increased from the driest phase, Phase 3 & 4 (0.037 1/yr), to the wettest phase, Phase 6 (0.127 1/yr). The LFG modeling and findings from this study can assist with developing moisture enhancement strategies for bioreactor landfills and assessing LFG collection data to support claims of enhanced waste decomposition and stabilization.
Keywords: landfill; methane; organic stability; landfill gas; bioreactor; municipal solid waste